The Role of Cerebellar Structural Plasticity and Astrocytic Activity in Motor-Skill Learning - (:unkn) unknown (My University, 2020)
Motor-skill learning is associated with cerebellar synaptogenesis and astrocytic hypertrophy, but most of these assessments of cerebellar ultrastructure have been completed after one month of training. After one month of training, the motor-skills necessary to complete these tasks have been acquired for weeks. Furthermore, the contributions of cerebellar astrocytes to motor-skill learning remains largely unexamined. The first experiment of this dissertation aimed to characterize cerebellar ultrastructure during the acquisition phase of motor-skill learning, at a point when motor performance is still improving. The second experiment aimed to examine the contributions of cerebellar astrocytes to motor-skill learning by activating astrocytic Gi-signaling during acrobatic training and then assessing its impact on behavior and cerebellar ultrastructure. In both experiments, male and female rats trained for four days on the acrobatic motor learning task, which involved traversing challenging obstacles such as narrow beams and ladders. Concurrently, rats in the motor control condition walked a flat alleyway requiring no skilled movements. After training was complete, all rats were euthanized, and tissue was prepared for electron microscopy. Unbiased stereology techniques were used to assess synaptic and astrocytic plasticity. The first experiment revealed that female rats made fewer errors and had shorter latencies on the acrobatic course compared to male rats. Male and female rats that completed four days of acrobatic training both displayed an increase in the density of parallel fiber-Purkinje cell synapses per Purkinje cell and an increase in astrocytic volume, relative to rats in the motor control group. The second experiment where the rats that trained on the acrobatic course expressed either an astrocytic mCherry control virus or hM4Di DREADD virus revealed that activation of Gi-signaling during acrobatic training increased the number of missteps per trial and the latency to complete trials on the acrobatic course. Further motor performance testing indicated a motor coordination, rather than a motor learning deficit, is likely driving this behavioral effect. In addition, activation of astrocytic hM4Di DREADDs increased synaptogenesis and astrocyte volume independent of motor-skill learning. These experiments find that cerebellar plasticity happens rapidly following motor-skill learning and highlight the role of cerebellar astrocytes, a relatively understudied cell population, in motor behavior.